Escritas e desenhos de crianças negras: análise antirracista e afrocêntrica a partir de um projeto de dança - Oliveira, Cibelle de Paula (2022)
The research Writings and drawings of black children: anti-racist and afrocentric analysis from a dance project, has as a research problem: What are the reflections recorded by students that show anti-racist awareness in the school environment? The general objective is to analyze the productions of the participants of the project “Danças Populares Brasileiras: Corporeidade e Movimento” based on theoretical assumptions, which underlie the critical awareness of anti-racism and Afrocentric pedagogy in the school educational process. The specific objectives are: to analyze the legal frameworks that resulted in the consolidation of the mandatory teaching of African and Afro-Brazilian history and culture at all levels of education; present the pedagogical proposal and the methodological strategies of the project “Brazilian Popular Dances: Corporeity and Movement”, meeting the current legislation and the intention to work with Afro-Brazilian and African culture from the perspective of Project Pedagogy; interpret the records of the children participating in the project, analyzing the extent to which Afrocentric pedagogy contributes to the construction of the anti-racist consciousness of black and non-black children. The hypothesis is the reflection of anti-racism in the school environment from the recognition of the historical and cultural origin of Brazilian popular dances of African origins, which affect the awakening of their identity affirmation and the development of positive representation. The central concepts are: racism, anti-racism, identity and decolonial education, based on the authors Almeida (2019), Cavalleiro (2001), Gomes (2005) and Trindade (2010). This is a documentary research based on the analysis of the written records and drawings of the students that gradually incorporated a positive representation of their black identity and, at the same time, had a huge impact on their self-perception. As a result, the importance of legislations that make mandatory the education for ethnic-racial relations stands out because they guarantee the grounding for anti-racist practices. It has been observed that most students who participated in the project for two years or more developed reflections about their identitary belongingness, which leads us to conclude that anti-racist education is a process. The referential approach reflects possible ways for an education that values and potentializes the diversity and the fortification of children’s self-esteem, in opposition to the epistemicide that historically minimized the knowledge of Black women and researchers. Therefore, this research has a political commitment and is aligned with the new epistemological paths that value Black authorship, including children